Results from an Australopithecus africanus dental enamel fragment confirm the potential of palaeoproteomics for South African Plio-Pleistocene fossil sites - Palesa P. Madupe; Fazeelah Munir; Marc Dickinson; Alberto J. Taurozzi; Meaghan Mackie; Mirriam Tawane; Catherine Mollereau; Nomawethu Hlazo; Kirsty Penkman; Lauren Schroeder; Clément Zanolli; Jesper V. Olsen; et al. (South African Journal of Science)
The southern African Late Pliocene to Early Pleistocene hominin record is abundant and exhibits a high taxonomic diversity with three genera represented: Australopithecus, Paranthropus and Homo. Hominin fossil diversity and variation are often contextualised within other fossil assemblages or modern/extant counterparts. However, the incompleteness of the fossil record, sample selection bias and taphonomic condition of the specimens themselves constrain interpretations of diversity and variation within and between species. Thus, species identification and the nature of the observed variation are frequently debated. Palaeoproteomics can help improve our understanding of taxonomic variation, as demonstrated by the recently generated proteome of Paranthropus specimens from Swartkrans. Here, we demonstrate protein preservation for an A. africanus specimen from Sterkfontein Member 4, Sts 63, using minimally invasive analysis, and identify it as belonging to a male individual. We then discuss some of the current limitations of palaeoproteomics and how we can potentially overcome them. Although it is still in its infancy for Plio-Pleistocene hominin fossils, palaeoproteomics has the potential to help unravel the causes of observed morphological variation. Lastly, we strongly believe that the involvement of African researchers at all levels of this research, including leadership, is of great importance.